“Intervención de enfermería en paciente adulto con hemorragia gastrointestinal alta” - Jaramillo Torres, Johanna María (2024)
The purpose of this study was to determine the nursing interventions necessary for the hemodynamic stability of the patient with upper gastrointestinal bleeding. Since this pathology refers to blood loss occurring in the digestive tract from the esophageal sphincter to the angle of Treitz. This condition may present with symptoms such as hematemesis, melena and occasionally hematochezia. The main causes of this type of bleeding include peptic ulcers, esophagitis, gastritis, duodenitis, esophageal varices, Mallory-Weiss tears and digestive tumors. Based on the clinical history, the comprehensive nursing assessment was elaborated through Marjory Gordon's 11 functional patterns model, identifying the patient's specific needs in a timely manner, thus using the NANDA, NOC and NIC taxonomies. The nursing interventions received by the patient included: control of shock, fever, administration of blood products, pain relief and reduction of anxiety, which contributed significantly to the stabilization and improvement of the patient's health.These care plans led the patient to a favorable recovery, especially his gastrointestinal system, and prevented possible complications .The analysis of the results of the nursing care plans executed on the patient has been highly satisfactory, effectively fulfilling the established objectives.